(untitled) (Journal of Partial Differential Equations, 2001)
In this paper, a fundamental solution at the origin and mean value theorem of generalized Greiner operator are given. Then the Hardy type inequality and some Pohozaev type identities are proved. As their applications, some nonexistence results of semilinear nonelliptic equation and unique continuation are discussed.